2021
DOI: 10.1111/omi.12347
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a UbK family kinase in Porphyromonas gingivalis that phosphorylates the RprY response regulator

Abstract: Phosphorylation of proteins is a key component of bacterial signaling systems that can control important functions such as community development and virulence. We report here the identification of a Ubiquitous bacterial Kinase (UbK) family member, designated UbK1, in the anaerobic periodontal pathogen, Porphyromonas gingivalis. UbK1 contains conserved SPT/S, Hanks‐type HxDxYR, EW, and Walker A motifs, and a mutation analysis established the Walker A domain and the Hanks‐type domain as required for both autopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
(85 reference statements)
1
7
0
Order By: Relevance
“…On the other hand, processing of proRgpA is dependent on VimA. Furthermore, activation of gingipains is probably additionally reliant on a response regulator RprY (PGN_1186) that was found to be phosphorylated (Y 41 ) in our phosphoproteomic analysis (Table S1) in accordance with recent findings (Perpich et al, 2021;Shen et al, 2020). Regulation was observed at the mRNA level and included other T9SS cargo proteins such as PPAD (Shen et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, processing of proRgpA is dependent on VimA. Furthermore, activation of gingipains is probably additionally reliant on a response regulator RprY (PGN_1186) that was found to be phosphorylated (Y 41 ) in our phosphoproteomic analysis (Table S1) in accordance with recent findings (Perpich et al, 2021;Shen et al, 2020). Regulation was observed at the mRNA level and included other T9SS cargo proteins such as PPAD (Shen et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Although phosphorylation of histidine and aspartate is mostly reserved for two-component systems, the best characterized kinases target serine, threonine, and tyrosine residues (Whitmore & Lamont., 2012). Recently, a new class of bacterial kinases belonging to the ubiquitous bacterial kinase (UbK) family has been described (Nguyen et al, 2017;Perpich et al, 2021). UbKs have dual specificity and phosphorylate both Ser/Thr and Tyr residues.…”
mentioning
confidence: 99%
“…Structurally, UbK contains a conserved domain: the Walker A motif, HxDxYR, SPT/S and EW motifs. Ubk1 is a UbK family member in P. gingivalis that can autophosphorylate on the tyrosine and serine residues within the HxDxYR and SPT/S domains, respectively ( Perpich et al., 2021 ).…”
Section: The Structure Of Bacterial Tyrosine and Serine/threonine Kinases And Phosphatasesmentioning
confidence: 99%
“…gingivalis can also exert its pathogenic function. Specifically, RprY, an orphan two-component system response regulator, can be phosphorylated by UbK1 on Y41 residue, affecting its transcriptional function ( Shen et al., 2020 ; Perpich et al., 2021 ). The UbK in S. mutans has been reported associated with cell morphology and biofilm development ( Bitoun et al., 2014 ).…”
Section: The Function Of Oral Bacterial Tyrosine and Serine/threonine Kinases And Phosphatasesmentioning
confidence: 99%
“…Consistently, the RprY with a Y41F substitution impaired P. gingivalis virulence in a murine model of alveolar bone loss ( Shen et al, 2020 ). Furthermore, a recent report showed that the Tyr phosphorylation of RprY is mediated by the Ubiquitous bacterial Kinase 1 (UbK1) ( Perpich et al, 2021 ). In addition to Thr phosphorylation of SpxB, the Tyr phosphorylation at positions 409, 415, and 588 was also identified, with a possibly significant role in intraspecies and interspecies competition in S. sanguinis ( Mu et al, 2021 ).…”
Section: Major Ptms In Oral Bacteria and Their Functional Impactmentioning
confidence: 99%